Is Islamic banking customer innovativeness an important determinant of customers’ intention to adopt Islamic banking? - Gumela, Ahmad Muhammad; Othman, Mohammad Azmi; Mohd Yusof, Rosylin (2015)
The purpose of this study is to examine the influence Islamic banking customer innovativeness, attitude, social norm and intention to adopt Islamic banking. To achieve these objectives, 229 survey questionnaires from a full-fledge Islamic banking in Northern Nigeria were analyzed using structural equation modeling.Findings indicate that Islamic banking customer innovativeness, attitude and social norm positively predicted customers’ intention to adopt Islamic banking.Implications for Islamic marketing managers planning to introduce new products into a competitive world where market segmentation becomes indispensable are discussed.